Imunoexpressão da proteína endonuclease apurínica/apurimidínica (APE-1) em adenomas pleomórficos e carcinomas ex-adenomas pleomórficos - Silva, Leorik Pereira da (2016)
Introduction: Apurinic/Apyrimidinic Endonuclease 1 (APE-1) is an essential protein for DNA base excision repair (BER) pathway and regulation of redox activities. The ability of malignant cells to recognize and repair DNA damage is an important mechanism for tumor survival, and recent studies suggest that APE-1 overexpression is related to poor prognosis in some tumors. Purpose: To analyze the immunoreactivity of APE-1 in Pleomorphic Adenomas (PA) and Carcinomas Ex Pleomorphic Adenomas (CaExPA) of salivary glands. Materials and Methods: A total of 49 tumors fixed in formalin and embedded in paraffin (33 PA and 16 CaExPA) underwent immunohistochemical study by the immunoperoxidase technique. APE-1 immunoreactivity was evaluated quantitatively by the percentage of immunopositive cells. For statistical analysis a significance level of 5% (p≤ 0.05) was adopted. Results: All cases of PA and CaExPA (n=49) were positive for APE-1, however, there was a higher expression in CaExPA, with statistically significant difference (p<0.001). There was no association between APE-1 expression and tumors of major or minor salivary gland, however, not encapsulated PA (median expression = 54.2%) showed higher expression when compared to encapsulated tumors (p=0.02). APE-1 overexpression was found mainly in cases of CaExAP with lymph node metastasis (median expression = 90.3% - p=0.002) and invasive pattern (median expression = 89.9% - p=0.003), when compared to cases without metastasis and intracapsular pattern. Conclusion: This study suggests that APE-1 is deregulated in the studied tumors. The increased expression of APE-1 is associated with the absence of complete capsule in PA and it is associated with more aggressive behavior in CaExPA.